Peningkatan Kesejahteraan Pelaku UMKM Dasa Wisma Melalui Usaha Frozen Food “Mawar” di Desa Ngijo Karang Ploso Kabupaten Malang - Yunia Azis; Dede Ropik Yunusa (LOSARI DIGITAL, 2026)
UMKM are recognized as a sector capable of surviving various crises; however, they still face challenges in marketing, capital, and human resources. This community service activity aims to enhance the business capacity of Mawar Frozen Food through strengthening both production and marketing aspects. The method employed was a participatory approach consisting of observation, discussion, label design training using the Canva application, and the provision of a freezer. This approach was selected to ensure the active involvement of partners in every stage of the activity, so that the solutions provided are aligned with their actual needs. Evaluation was conducted using a before-after approach through observation, interviews, and comparison of sales data. The results indicate an increase in product storage capacity by 50% and a rise in weekly turnover from IDR 500,000 to IDR 720,000 (an increase of 44%). In addition, partners demonstrated improved skills in designing more informative and attractive product labels. Improvements in the visual aspects of the products also contributed to increased consumer trust and competitiveness in the local market. This activity has proven effective in enhancing the competitiveness and welfare of UMKM partners, as well as encouraging sustainable economic participation within the surrounding community.